EFEKTIVITAS APE MAZE TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN - Ruslige Juliarti Br.Silitonga lige; Audia Sianipar; Marshanda Octavia Fatma Yuslia; Meyliana Nursihab; Miftahul Jannah; Rr. Deni Widjayatri (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
This study aims to determine whether the Maze educational game tool is effective in improving the cognitive development of children aged 5-6 years. Cognitive aspect is one aspect of development in children that is important to be developed, which this aspect refers to the stage of the child's ability. The cognitive ability of children aged 5-6 years is where children can know numbers, so that children can determine the picture of numbers, can deal with problems seen in everyday life, children have understood the conditions and consistent results, and children can show exploratory exercises. The method used in this research is systematic literature or literature study, the literature used in the past 6 years. This research consists of 6 stages including: determining the title, exploring information, determining the direction of the research, collecting data, presenting data, and compiling reports. Based on the results of the literature above, it can be concluded that the effectiveness of the Maze Educational Game Tool (APE) is quite effective in helping to improve the Cognitive Development of Adult Children 5-6 years. It can be concluded that APE maze is able to help children's cognitive development well, such as helping children to practice problem solving skills, recognizing and knowing numbers, recognizing and mentioning number symbols and children can know various alphabets.